Impact of Specific Gravity on Soil Compaction Characteristics for Road-Base - Idiata, David; Kayode-Ojo, Ngozi; Okonofua, Ehizonomhen Solomon (Teknika, 2026)
This study investigates the role of specific gravity, maximum dry density (MDD), and optimum moisture content (OMC) in evaluating soil compaction for road base construction using samples from three groups and a control. Group 3 exhibited the highest specific gravity (2.61), consistent MDD (2.03 g/cm³), and low OMC (10.25%), indicating ideal granular properties. Group 1, with slightly lower specific gravity (2.54), achieved the highest MDD (2.04 g/cm³) and stable OMC (10%), suggesting good compaction due to favorable gradation. Group 2, despite moderate specific gravity (2.57), had the lowest MDD and highest OMC, pointing to fine, moisture-sensitive soils. The Control group showed moderate compaction but high variability. Correlation analysis revealed weak, insignificant relationships between specific gravity and compaction parameters, highlighting the influence of other factors like grain size and plasticity. The study concludes that specific gravity is important but should be assessed with other soil properties. Group 3 and Group 1 are most suitable for direct use.